2012
DOI: 10.2478/s11686-012-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Mawsonascaris parva sp. nov. (Nematoda: Ascaridida) from the Arabian whipray Himantura randalli Last, Manjaji-Matsumoto et Moore (Rajiformes: Dasyatidae) off the coast of Iraq

Abstract: Mawsonascaris parva sp. nov. collected from the Arabian whipray Himantura randalli Last, Manjaji-Matsumoto et Moore (Rajiformes: Dasyatidae) off the coast of Iraq is described and illustrated using light and scanning electron microscopy. The new species differs from its congeners by its small body size (8.11-18.2 mm long), the absence of an intestinal caecum, the slightly unequal spicules (left and right spicule 1.08-2.50 mm and 0.98-2.01 mm long, respectively, representing 12.1-13.7% and 10.1-12.1% of body le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, in the present study, in one individual, we found the left spicule to be only approximately 1.2 times longer than the right. The relative length of the left and right spicules is a diagnostic morphological character for distinguishing and identifying species of this genus (Sprent, 1990; Ali et al ., 2012; Li et al ., 2012). The molecular analysis showed a low level of nucleotide variation in the ITS (only 0.10% nucleotide divergence) and cox 1 sequences (only 1.04–2.08% nucleotide divergence) between the two different morphotypes, which is far lower than the interspecific nucleotide variations between M. australis and P. rajae / P. argentinensis recorded in GenBank (14.1% nucleotide differences in the ITS region; >30.0% nucleotide differences in the cox 1 region).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, in one individual, we found the left spicule to be only approximately 1.2 times longer than the right. The relative length of the left and right spicules is a diagnostic morphological character for distinguishing and identifying species of this genus (Sprent, 1990; Ali et al ., 2012; Li et al ., 2012). The molecular analysis showed a low level of nucleotide variation in the ITS (only 0.10% nucleotide divergence) and cox 1 sequences (only 1.04–2.08% nucleotide divergence) between the two different morphotypes, which is far lower than the interspecific nucleotide variations between M. australis and P. rajae / P. argentinensis recorded in GenBank (14.1% nucleotide differences in the ITS region; >30.0% nucleotide differences in the cox 1 region).…”
Section: Discussionmentioning
confidence: 99%
“…Species of Mawsonascaris Sprent, 1990 are rare ascaridoid nematodes, occurring in the digestive tract of elasmobranchs (Sprent, 1990; Ali et al ., 2012; Li et al ., 2012). To date, only six species have been reported, namely M. australis (Johnston & Mawson, 1943), M. laymani (Mozgovoy, 1950), M. pastinacae (Rudolphi, 1819), M. zhoui Li, Xu & Zhang, 2012, M. myliobatum (Yin & Zhang, 1983) and M. parva Ali, Zhang, Al-Salim & Li, 2012, from the Atlantic Ocean, Arabian Gulf, and Australian and Chinese waters (Johnston & Mawson, 1943; Mozgovoy, 1950; Yin & Zhang, 1983; Sprent, 1990; Ali et al ., 2012; Li et al ., 2012). During a helminthological survey of Chinese marine fishes, several nematode specimens, identified morphologically as M. australis, were collected from the brown guitarfish Rhinobatos schlegelii Müller & Henle (Rhinopristiformes: Rhinobatidae) in the Taiwan Strait.…”
Section: Introductionmentioning
confidence: 99%